1995
DOI: 10.1590/s0102-311x1995000200018
|View full text |Cite
|
Sign up to set email alerts
|

On the controversy about the efficacy of the antimeningococcal B vaccine: methodological pitfalls

Abstract: The present communication analyses methodological problems related to evaluating the protection given by the antimeningococcal B vaccine to children under four years of age in a case-control study carried out in Sao Paulo, Brazil. Detection of a hospital selection bias, among other disturbing features of the study, suggests that the efficacy of the vaccine was underestimated. Altogether, data presented support a wider use of the Cuban-produced vaccine to reduce morbidity and mortality from serogroup B meningoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…The effectiveness reported against serogroup B was 72% in children between 6 and 83 months of age. 23 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effectiveness reported against serogroup B was 72% in children between 6 and 83 months of age. 23 …”
Section: Resultsmentioning
confidence: 99%
“…For the prospective part, the estimated and actual coverage were 93% and 92% respectively, and effectiveness increased to 55%. 20 , 23 …”
Section: Resultsmentioning
confidence: 99%
“…10,11 Because it is a detergent extracted OMV-based vaccine, the protective activity induced by this preparation is mainly targeted against homologous strains. 10,[13][14][15] Nevertheless, some cross-reactive immune responses can be observed in clinical trials with this vaccine candidate, which are presumably induced by minor proteins. This hypothesis is supported by the finding of Williams et al (2014), 16 who observed this type of crossresponse against proteins other than the major antigens of meningococcus.…”
Section: Introductionmentioning
confidence: 99%
“…Although the circulating strains were not specifi ed in these studies, they were likely similar to those isolated in Sao Paulo, with wide circulation of heterologous strains. [23,25] When Brazil's Ministry of Health assessed the impact of vaccination with VA-MENGOC-BC in 6 Brazilian states, including those referred to here, it reported effectiveness against serogroup B as 72% (CI 63%-80%) in children aged 6-83 months. [25] The effectiveness found in Brazil is high, especially considering the country's geographical and epidemiological characteristics.…”
Section: Peer Reviewedmentioning
confidence: 98%
“…[23,25] When Brazil's Ministry of Health assessed the impact of vaccination with VA-MENGOC-BC in 6 Brazilian states, including those referred to here, it reported effectiveness against serogroup B as 72% (CI 63%-80%) in children aged 6-83 months. [25] The effectiveness found in Brazil is high, especially considering the country's geographical and epidemiological characteristics. The great diversity of meningococcal serosubtypes supports the contention that VA-MENGOC-BC induced crossreactive protection in the age groups assessed.…”
Section: Peer Reviewedmentioning
confidence: 98%